2013
DOI: 10.1111/trf.12257
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing donor selection for public cord blood banking: influence of maternal, infant, and collection characteristics on cord blood unit quality

Abstract: Background Banked unrelated donor umbilical cord blood (CB) has improved access to hematopoietic stem cell transplantation for patients without a suitably matched donor. In a resource-limited environment, ensuring that the public inventory is enriched with high-quality cord blood units (CBUs) addressing the needs of a diverse group of patients is a priority. Identification of donor characteristics correlating with higher CBU quality could guide operational strategies to increase the yield of banked high-qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
108
5
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(135 citation statements)
references
References 30 publications
5
108
5
15
Order By: Relevance
“…Large studies have reported several maternal, fetal and obstetrical factors impacting CB cell yield. [4][5][6] Recently, it has been documented in adult individuals that hematopoietic stem and progenitor cells circulate from the bone marrow to the peripheral blood according to a circadian rhythm, 7 leading to circadian variations in their concentrations in blood (reviewed by ).…”
mentioning
confidence: 99%
“…Large studies have reported several maternal, fetal and obstetrical factors impacting CB cell yield. [4][5][6] Recently, it has been documented in adult individuals that hematopoietic stem and progenitor cells circulate from the bone marrow to the peripheral blood according to a circadian rhythm, 7 leading to circadian variations in their concentrations in blood (reviewed by ).…”
mentioning
confidence: 99%
“…Birth weight, 6,7,23 length 8 and gender 4,10,17,24 have been correlated with CBU volume and TNCC; as well as different obstetric parameters, such as placenta weight, 17 time of cord clamping and time of UCB collection after birth. 17,23,25 A Canadian study showed that birth weights from different ethnic groups are significantly different, and encouraged modification of birth weight curves according to ethnicity; it is interesting to note that Middle Eastern and North African populations present the closest mean birth weight to European and Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Bone Marrow Donors Worldwide collaboration of registries presents a lack of genetic diversity with an over-representation of donors from Northwestern European descent. 4,6,7,[10][11][12][13][14] Thus, patients with non-European ancestry have lower odds of obtaining a graft with high HLA compatibility and/or high TNCC. [13][14][15][16] These studies highlight the importance of developing CB banking in partnership with birth clinics that care for pregnant women originating from populations that are underrepresented in existing CBBs and registries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations